Regional business cycle and growth features of Japan - Masaru Inaba; Keisuke Otsu (University of Kent, School of Economics, 2017)
We study the features of regional business cycles and growth in Japan. We find evidence of unconditional convergence over the 1955-2008 period. For the 1975-2008 period, we find evidence of convergence conditional on TFP gap, population growth, private investment rate and TFP growth. We also find that the consumption-output correlation puzzle exists, which implies that the idiosyncratic income shocks are not shared among prefectures and regions. Our analysis implies that frictions in financial markets are responsible for the low consumption risk-sharing among prefectures.
Keywords: E01; E32; O47; 330; Japanese Economy; Regional Convergence; Regional Business Cycle Synchronization